2019
DOI: 10.2196/preprints.17101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Blended Learning System to Improve Motivation, Mood State, and Satisfaction in Undergraduate Students: Randomized Controlled Trial (Preprint)

Abstract: BACKGROUND Smartphone-based learning, or mobile learning (m-learning), has become a popular learning-and-teaching strategy in educational environments. Blended learning combines strategies such as m-learning with conventional learning to offer continuous training, anytime and anywhere, via innovative learning activities. OBJECTIVE The main aim of this work was to examine the short-term (ie, 2-w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The studies included students at the bachelor's/undergraduates (n = 17), master's/ entry level (n = 1) and DPT programme level (n = 4). Of the included studies, ve were from Australia (25)(26)(27)(28)(29), ve from Spain (30)(31)(32)(33)(34), three from Brazil (35)(36)(37), one from Denmark (38) and eight from the USA (39)(40)(41)(42)(43)(44)(45)(46). Seventeen of the studies had an RCT design (25,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), and ve were cohorts (26,(43)(44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies included students at the bachelor's/undergraduates (n = 17), master's/ entry level (n = 1) and DPT programme level (n = 4). Of the included studies, ve were from Australia (25)(26)(27)(28)(29), ve from Spain (30)(31)(32)(33)(34), three from Brazil (35)(36)(37), one from Denmark (38) and eight from the USA (39)(40)(41)(42)(43)(44)(45)(46). Seventeen of the studies had an RCT design (25,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42), and ve were cohorts (26,(43)(44)(45)(46).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed overview of the included studies is shown in Table 2. For the 10 studies that were similar in terms of design, population, interventions and outcomes, we conducted meta-analyses using RevMan 5.3 software (Cochrane Community worldwide) (27,28,(30)(31)(32)(33)(34)(44)(45)(46). Twelve studies were too heterogeneous and were not included in the meta-analyses (25,26,29,(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations